2007
DOI: 10.1186/1477-3163-6-4
|View full text |Cite
|
Sign up to set email alerts
|

Colon-available raspberry polyphenols exhibit anti-cancer effects on in vitro models of colon cancer

Abstract: BackgroundThere is a probable association between consumption of fruit and vegetables and reduced risk of cancer, particularly cancer of the digestive tract. This anti-cancer activity has been attributed in part to anti-oxidants present in these foods. Raspberries in particular are a rich source of the anti-oxidant compounds, such as polyphenols, anthocyanins and ellagitannins.MethodsA "colon-available" raspberry extract (CARE) was prepared that contained phytochemicals surviving a digestion procedure that mim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
85
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 68 publications
17
85
0
1
Order By: Relevance
“…It is also possible that differential cytotoxicity could be only elicited at the lower fruit extracts concentrations and the higher fruit concentrations might show cytotoxicity to normal cells. Our observations of high antioxidant and antiproliferative activity of R. ellipticus are in consonance with the previous studies on various species of raspberries, including yellow raspberry, which showed high polyphenol contents and their high antioxidant capacities and antiproliferative activities (Wang and Lin 2000;Ross et al 2007;Coates et al 2007;Weber et al 2008;Gansch et al 2009;Rao and Snyder 2010;Gulcin et al 2011). Significantly higher contents of polyphenols and their antioxidant capacities and anticancer activities observed in the yellow Himalayan raspberry R. ellipticus in the present study were much higher than those reported earlier for yellow raspberry Gansch et al 2009).…”
Section: Hplc Analysis Of Phenolic Compoundssupporting
confidence: 92%
“…It is also possible that differential cytotoxicity could be only elicited at the lower fruit extracts concentrations and the higher fruit concentrations might show cytotoxicity to normal cells. Our observations of high antioxidant and antiproliferative activity of R. ellipticus are in consonance with the previous studies on various species of raspberries, including yellow raspberry, which showed high polyphenol contents and their high antioxidant capacities and antiproliferative activities (Wang and Lin 2000;Ross et al 2007;Coates et al 2007;Weber et al 2008;Gansch et al 2009;Rao and Snyder 2010;Gulcin et al 2011). Significantly higher contents of polyphenols and their antioxidant capacities and anticancer activities observed in the yellow Himalayan raspberry R. ellipticus in the present study were much higher than those reported earlier for yellow raspberry Gansch et al 2009).…”
Section: Hplc Analysis Of Phenolic Compoundssupporting
confidence: 92%
“…Several studies have indicated the anti-cancer potential of polyphenolic compounds, and in particular their ability to inhibit the proliferation of cancer cells via their effects on the cell-cycle and/or apoptosis (Lee et al, 2006;Ramos, Rodríguez-Ramiro, Martín, Goya, & Bravo, 2011;Vu et al, 2012), and have suggested their use as novel dietary chemopreventive agents (Araújo, Gonçalves, & Martel, 2011). For example, the antiproliferative effects of polyphenolic extracts from olive oil (Corona et al, 2007), red wine (Gómez-Alonso et al, 2012), tomato (Saunders, 2009), araçá (Medina et al, 2011), raspberry (Coates et al, 2007) and cranberry (Vu et al, 2012) have been reported. However, to date there are no previous data on the actions of grape pomace extracts, although their potential to protect against oxidative stress has been shown in Caenorhabditis elegans (Jara- Palacios et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This anticancer activity has been attributed by the anti-oxidant components of this food. Raspberry extract, bioavailable in colon contains phyto-chemicals surviving the digestion procedure that mimicked the physiochemical conditions of the upper gastro intestinal tract [26]. The polyphenol rich extract is assessed for anticancer properties in a series of in vitro systems that serve as model for important stages of colon carcinogenesis, initiation and invasion.…”
Section: Raspberry Extract:-mentioning
confidence: 99%